IMPLEMENTASI WEBSITE LAYANAN KESEHATAN MENTAL BERBASIS SELF-ASSESSMENT DENGAN CHATBOT AI MENGGUNAKAN NATURAL LANGUAGE PROCESSING - Agung Kurniawan; Meidy Fajar Wahyu (PT. ALRCA INOVASI DIGITAL, 2026)
This study implemented a web-based mental health service platform that integrates self-assessment, an NLP-based chatbot, and centralized data storage for a mental health clinic in Pasar Kemis, Tangerang, Banten. The research addressed manual recording, limited early-screening access, service delays, and the absence of an integrated mechanism for receiving complaints and scheduling counseling. The system was developed through observation, interviews, literature study, database design, interface design, implementation, and system testing. The website provides user registration, screening, chatbot consultation, educational articles, counseling booking, and administrative management of users, schedules, assessments, and chat logs. The implemented system stores self-assessment results, chatbot interaction history, and user profiles in a structured database to support more organized service workflows. Testing and user feedback reported in the study indicate that the system functions as expected and is positively received in terms of usability, accessibility, and chatbot usefulness. The study concludes that the proposed platform can improve the efficiency, structure, and accessibility of early mental health services.